Reconstitution of Functional Integrin αIIbβ3 and Its Activation in Plasma Membrane-Mimetic Lipid Environments - Una Janke; Alexandra Mitlehner; Aileen Weide; Theresia Gutmann; Mihaela Delcea (Membranes, 2021)
The study of the platelet receptor integrin αIIbβ3 in a membrane-mimetic environment without interfering signalling pathways is crucial to understand protein structure and dynamics. Our understanding of this receptor and its sequential activation steps has been tremendously progressing using structural and reconstitution approaches in model membranes, such as liposomes or supported-lipid bilayers. For most αIIbβ3 reconstitution approaches, saturated short-chain lipids have been used, which is not reflecting the native platelet cell membrane composition. We report here on the reconstitution of label-free full-length αIIbβ3 in liposomes containing cholesterol, sphingomyelin, and unsaturated phosphatidylcholine mimicking the plasma membrane that formed supported-lipid bilayers for quartz-crystal microbalance with dissipation (QCM-D) experiments. We demonstrate the relevance of the lipid environment and its resulting physicochemical properties on integrin reconstitution efficiency and its conformational dynamics. We present here an approach to investigate αIIbβ3 in a biomimetic membrane system as a useful platform do dissect disease-relevant integrin mutations and effects on ligand binding in a lipid-specific context, which might be applicable for drug screening.